Major court and tribunal decisions in Australia in 2014. (June 2015) - Forsyth, Anthony
The year 2014 saw the long-awaited ruling by the High Court of Australia on whether an implied term of mutual trust and confidence exists in employment contracts. In unanimously finding against the existence of such a term, in Commonwealth Bank of Australia v Barker (2014) 312 ALR 356, the Court has taken the common law of employment in Australia in a profoundly different direction from that of the United Kingdom. The year also witnessed several other significant decisions dealing with the contract of employment, the general protections provisions of the Fair Work Act 2009 (Cth) and the new anti-bullying jurisdiction of the Fair Work Commission. Major decisions in 2014 also addressed key features of the statutory framework for enterprise agreements and collective bargaining, as well as penalty rates under modern awards.